2019
DOI: 10.1145/3359208
|View full text |Cite
|
Sign up to set email alerts
|

Design for Collaborative Information-Seeking

Abstract: Although Collaborative Information-Seeking (CIS) is becoming prevalent as people engage in shared decision-making, interface components adopted in the most commonly used information seeking tools (e.g., search, filter, select, and sort) are designed for individual use. To deepen our understanding of (1) how such single-user designs affect people's consensus building processes in CIS and (2) how to devise an alternative design to improve current practices, we conducted two 4-week diary studies and observed how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…From the perspective of CSCW and Groupwork: collaboration in job-seeking can make the job-seeker achieve better outcomes (as per server studies indicate [46,68,78]), common challenges in groupwork are cost for communication [32] and group awareness [31]. From the angle of collaborative job-seeking for people with autism, we found that career experts are rather scarce and many of our participants didn't have a chance to work with them.…”
Section: Implications For Future Designmentioning
confidence: 78%
See 1 more Smart Citation
“…From the perspective of CSCW and Groupwork: collaboration in job-seeking can make the job-seeker achieve better outcomes (as per server studies indicate [46,68,78]), common challenges in groupwork are cost for communication [32] and group awareness [31]. From the angle of collaborative job-seeking for people with autism, we found that career experts are rather scarce and many of our participants didn't have a chance to work with them.…”
Section: Implications For Future Designmentioning
confidence: 78%
“…Exploring collaborative job seeking for people with autism introduces novel perspectives for Human-Computer Interaction research domains. Specifically, while a large body of research in Computer-Supported Cooperative Work (CSCW) focusing on learning how groups work in varying contexts of collaboration [6,32], the ways people with autism coordinate their task dependencies [50,57], define division of work [59], build group awareness of activities and plan [27,31], and sharing skills, knowledge, and experience [38] under collaborative job seeking is not well understood. Further, from the perspective of assistive computing, understanding the status quo of collaborative job seeking for people with autism provides new avenues of research for designing technologies that mitigate common challenges identified in former studies, including executive planning [45,49,81], emotional regulation [52,75,76,88], and communication differences [10,70,73].…”
Section: Introductionmentioning
confidence: 99%
“…All forms of collaboration stem from a similar motivation; group work can be productive because it allows individuals to share and gain insights they might not have discovered independently [13]. By pooling the knowledge and expertise of all members, group work can be executed more efficiently and accurately [6,16,26,27]. Several studies in HCI, especially Computer-Supported Cooperative Work (CSCW), have built interactive systems and designs that apply in group work settings, such as collaborative searching, collaborative information seeking, and beyond [2,9,27,52,54].…”
Section: Related Workmentioning
confidence: 99%
“…By pooling the knowledge and expertise of all members, group work can be executed more efficiently and accurately [6,16,26,27]. Several studies in HCI, especially Computer-Supported Cooperative Work (CSCW), have built interactive systems and designs that apply in group work settings, such as collaborative searching, collaborative information seeking, and beyond [2,9,27,52,54]. In the research on data annotation interfaces, a line of studies apply the spirit of group work-"the whole is greater than the sum of its parts"-especially when the ground truth is not deterministic and individual viewpoints can matter.…”
Section: Related Workmentioning
confidence: 99%
“…As the literature in CSCW and social computing grows, sensemaking has influenced on developing social information foraging theory [49]. Social information foraging has largely influenced in designing CSCW applications, including collaborative information seeking [31,32], collaborative data analytics [69], collaborative search [45], social network question and answering [46], and beyond [9,70]. 3D printing troubleshooting is achieved largely by active interaction between a novice and an advanced users in a remote setting using the information repository built based on social annotation [40].…”
Section: Related Workmentioning
confidence: 99%